2019
DOI: 10.1103/physrevlett.122.095501
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Topological Edge Modes in a Quasiperiodic Acoustic Waveguide

Abstract: Topological boundary and interface modes are generated in an acoustic waveguide by simple quasiperiodic patterning of the walls. The procedure opens many topological gaps in the resonant spectrum and qualitative as well as quantitative assessments of their topological character are supplied. In particular, computations of the bulk invariant for the continuum wave equation are performed. The experimental measurements reproduce the theoretical predictions with high fidelity. In particular, acoustic modes with hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 40 publications
0
61
0
Order By: Relevance
“…Topological states have been successfully observed in several platforms [13][14][15][16][17][18][19][20][21], and have been pursued to achieve robust, diffraction-free wave motion. Additional functionalities have been explored in the context of topological pumping [22][23][24][25][26], quasi-periodicity [27][28][29], and non-reciprocal wave propagation in active [30][31][32][33][34][35][36] or passive non-linear [37][38][39][40] systems. These works and the references therein illustrate a wealth of strategies for the manipulation of elastic and acoustic waves, and suggest intriguing possibilities for technological applications in acoustic devices, sensing, energy harvesting, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Topological states have been successfully observed in several platforms [13][14][15][16][17][18][19][20][21], and have been pursued to achieve robust, diffraction-free wave motion. Additional functionalities have been explored in the context of topological pumping [22][23][24][25][26], quasi-periodicity [27][28][29], and non-reciprocal wave propagation in active [30][31][32][33][34][35][36] or passive non-linear [37][38][39][40] systems. These works and the references therein illustrate a wealth of strategies for the manipulation of elastic and acoustic waves, and suggest intriguing possibilities for technological applications in acoustic devices, sensing, energy harvesting, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the work 27 , there is no limitation on the number of phason configuration, though we found that taking measurement for 48 phason values is sufficient to clearly resolve the edge spectrum with better resolution than the one in ref. 27 . Followed the same procedure as one in measuring butterfly spectrum, the acoustic DOS for each value was obtained.…”
Section: Resultsmentioning
confidence: 66%
“…Nevertheless, the possibility of implementing the operator with quasiperiodic 1D platforms opens up new ways to observe and study the associated topological phenomena. A number of theoretical and experimental works have recently induced quasiperiodicity in a broad variety of systems 7,[21][22][23][24][25][26][27] to explore topological phase transitions and edge states. Even more, topological phases in higher dimensions 23,[28][29][30][31] have been predicted and the those characterized by second class Chern number in 2D quasiperiodic crystals observed experimentally 21,22 .…”
mentioning
confidence: 99%
“…This strategy, which allows us to interpret physical phenomena associated with a family of one-dimensional systems as consequences of higher-dimensional physics, has already been exploited in a variety of prior works, for example [41][42][43], although not directly in the specific form of Eq. (1).…”
Section: Design Of a Z 2 Weyl Hamiltonianmentioning
confidence: 99%